In search of the feeling of 'belonging' in higher education: undergraduate students transition into higher education. Issue 10 (26th November 2019) - Meehan, Catherine; Howells, Kristy
ABSTRACT: Previous research that evaluated first year students' transition into university found that the values of 'being, belonging and becoming' were important in particular within the first few months and within the first year of university. From our previous work, we reported that three things matter to students: the academic staff they work with, the nature of their academic study and the feeling of belonging. This paper provides a further illumination to our work by reporting on the qualitative data collected in the same study. The study included 530 students from five cohorts over a five-year period. As part of the Student Experience Evaluation instrument, open-ended questions probed students about their early experiences of belonging and transition into university. This original research uses rich data to illuminate the scales and items from previous quantitative data analysis to explore 'belonging', triangulated with research from the field. This paper is timely due to increased emphasis placed on learning and teaching with the introduction of the Teaching Excellence Framework. Student satisfaction is not a simplistic measure and this study articulates the complexity of student belonging in Higher Education.